THE BEDANA DANCE OF OLOK GADING AS A MEDIUM FOR CHARACTER EDUCATION IN CULTURAL PRESERVATION - M. Arie Zainun Najib; Malarsih (RADJA PUBLIKA, 2026)
The Bedana Negeri Olok Gading dance is a traditional art form from Lampung that functions not only as an aesthetic expression but also as a medium for character education. However, in contemporary practice, the Bedana dance is often positioned solely as a ceremonial performance, while its potential as a character education medium remains underutilized. This study aims to identify character education values embedded in the Bedana Negeri Olok Gading dance, analyze its function as a character education medium, and examine its role in preserving local culture. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through participant observation, in-depth interviews with artists and traditional leaders, and performance documentation. Data analysis involved data reduction, data display, and conclusion drawing, grounded in character education and arts education theories. The findings indicate that the Bedana Negeri Olok Gading dance embodies values such as religiosity, discipline, responsibility, togetherness, and politeness, internalized through movement structures, musical accompaniment, and social performance contexts. This study emphasizes the role of Bedana dance as a contextual and sustainable medium for character education in local cultural preservation.